Synthesis and characterization of functionalized molecular and macromolecular double-decker silsesquioxane systems. Issue 12 (26th January 2016) - Żak, P.; Majchrzak, M.; Wilkowski, G.; Dudziec, B.; Dutkiewicz, M.; Marciniec, B.
Abstract : Synthesis and characterization of new, molecular and macromolecularDDSQ -based compounds functionalized by substituted styrenes and distyrylarenes (also with heteroatoms) in a stereoselective manner is presented. Abstract : Synthesis and characterization of new, molecularDDSQ -based compounds functionalized by substituted styrenes (also with heteroatoms) in a stereoselective manner is presented. Additionally, a novel class of vinylene-arylene linear copolymers with double-decker silsesquioxane fragments in the main chain is developed. These molecular and macromolecular compounds were synthesized via efficient and highly stereoselective silylative coupling (and copolycondensation) and cross-metathesis (andADMET ) reactions.